Menulis Deskripsi dengan Model Investigasi Kelompok - Ridwan Ridwan (Kantor Bahasa Provinsi Maluku Utara, 2013)
Writing is the way to transform an idea or message to the readers. The act of writing in this research isdescriptive writing. The descriptive writing aims to write an object so the reader can feel and see the object bythemselves. This research is known as class action research. The class action research is conducted by using group investigation learning model: the PTK action comprisies two cycles, every cycle consists of three times of meetings. Every cycle includes planning, action, reflection, and evaluation. The results of the research show that the group investigation learning model could improve descriptive writing skills of Indonesian letter studies. These things are shown in the learning process until evaluation.